Between-Leg Mechanical Differences as Measured by the Bulgarian Split-Squat: Exploring Asymmetries and Relationships with Sprint Acceleration - Robert G. Lockie; Fabrice G. Risso; Adrina Lazar; Dominic V. Giuliano; Alyssa A. Stage; Tricia M. Liu; Megan D. Beiley; Jillian M. Hurley; Ibett A. Torne; John J. Stokes; Samantha A. Birmingham-Babauta; DeShaun L. Davis; et al. (MDPI AG, 2017)
Between-leg strength differences can negatively influence sprint acceleration. The challenge is to find a method to measure this within a unilateral exercise. This study analyzed a five repetition-maximum (5RM) Bulgarian split-squat (BSS) to identify between-leg differences for the dominant and non-dominant legs in peak and mean power, force, and velocity as measured by a linear position transducer. Between-leg differences in these variables were correlated with 20-m (0-5, 0-10, 0-20 m intervals) sprint velocity. Eight men were assessed in the 5RM BSS and 20-m sprint. T-tests calculated between-leg differences in power, force, and velocity. Spearman's correlations calculated relationships between the between-leg differences in the mechanical variables with velocity over each interval. When comparing the dominant and non-dominant legs, there were significant (p = 0.002-0.056) differences in 11 of 12 variables. However, percentage differences were low (~0.3-12%). There was one large, non-significant correlation (best repetition mean force between-leg difference and 0-5 m velocity; ρ = −0.810) out of 36 relationships. The BSS can provide a profile of between-leg differences in power, force, and velocity. There were limited relationships between the BSS between-leg differences and 20-m sprint velocities. Smaller between-leg differences in BSS power, force, and velocity could ensure minimal impact on acceleration.